Covid-19 y su incidencia en las buenas prácticas odontológicas - María Mercedes Calderón Paz (2022)
ABSTRACT: Dental care has been limited as a result of the outbreak of the rapidly spreading COVID- 19 epidemic, declared by the WHO as a public health emergency and therefore of global concern. Therefore, it is necessary to apply a checklist to establish good dental practices suggested by the WHO and the MSP to reduce the risk of cross-infection. The dentist and his team are exposed daily to aerosols and contact with probably contaminated body fluids. The general objective of this work was to analyze the incidence of COVID-19 in good dental practices. The methodology used was documentary based on collecting information and reading scientific articles on dentistry with quality and impact indicators and published on the digital platforms Scimago, Journal, Elsevier, and PubMed. The 73 selected papers established inclusion and exclusion search parameters. In conclusion, 43 articles have an impact factor Q1. The months of May and July have the most remarkable circulation; the origin corresponds to the United Kingdom with 17 pieces, followed by the United States with 16 and China with 10. A checklist was proposed to verify good dental practices, the application of the protocol, and biosafety measures before, during, and after the procedure, and to reduce the risk of cross-infection during the pandemic. Keywords: COVID-19, good dental practices, scientific articles